2022
DOI: 10.3390/life12081169
|View full text |Cite
|
Sign up to set email alerts
|

Soil Mycobiome Diversity under Different Tillage Practices in the South of West Siberia

Abstract: Managing soil biodiversity by reduced or no tillage is an increasingly popular approach. Soil mycobiome in Siberian agroecosystems has been scarcely studied; little is known about its changes due to tillage. We studied mycobiome in Chernozem under natural steppe vegetation and cropped for wheat by conventional or no tillage in a long-term field trial in West Siberia, Russia, by using ITS2 rDNA gene marker (Illumina MiSeq sequencing). Half of the identified OTUs were Ascomycota with 82% of the total number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Most of the studies analysing fungal communities in agricultural soils found Sordariomycetes as the dominant class, followed by other classes of Ascomycota, like Dothideomycetes and Eurotiomycetes. Agaricomycetes often account for much less than 10% of relative abundance (Balami et al, 2021 ; Clocchiatti et al, 2021 ; Dang et al, 2018 ; Fraç et al, 2018 ; Klaubauf et al, 2010 ; Naumova et al, 2022 ). The soil amendment with wood‐based materials, such as beech, seems to lead to an increase in Agaricomycetes (Clocchiatti et al, 2023 ; Malewski et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies analysing fungal communities in agricultural soils found Sordariomycetes as the dominant class, followed by other classes of Ascomycota, like Dothideomycetes and Eurotiomycetes. Agaricomycetes often account for much less than 10% of relative abundance (Balami et al, 2021 ; Clocchiatti et al, 2021 ; Dang et al, 2018 ; Fraç et al, 2018 ; Klaubauf et al, 2010 ; Naumova et al, 2022 ). The soil amendment with wood‐based materials, such as beech, seems to lead to an increase in Agaricomycetes (Clocchiatti et al, 2023 ; Malewski et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Spain, the vineyard tillage inhibited the diseaseresistant Trichoderma populations in the soil [139], which makes us wonder whether NT would boost beneficial fungi to attain the disease-suppressive soil [140]. In the south of West Siberia, half of the identified OTUs (operational taxonomic units) were Ascomycota [13], and the phyla Basidiomycota, Zygomycota, Mortierellomycota, Chytridiomycota, and Glomeromycota showed tillage-related differential abundance. Wheat residues could increase the abundance of dominant genera Mortierella, Chaetomium, Clonostachys, Gibberella, Fusarium, and Hypocrea as compared with undisturbed soil.…”
Section: Fungimentioning
confidence: 99%
“…Such concerns have led to the search for tillage systems that minimize negative impacts on the environment while cost-effectively sustaining crop productivity [8]. Conservation tillage techniques, such as minimum tillage (MT ≈ reduced tillage (RT)) [9], no-tillage (NT; zero tillage) [10], and organic mulch [11,12], minimize the impacts of tillage on soil structure and soil biota [13], reduce soil erosion threats, increase soil organic carbon (SOC) [1], and may help reduce GHG emissions in comparison to conventional tillage (CT) [14]. To achieve these goals, conservation tillage should be adapted in terms of local conditions and flexibly implemented in crop production systems.…”
Section: Introductionmentioning
confidence: 99%
“…The area where the field trial was performed was described earlier in our report about soil mycobiomes [10] (https://www.mdpi.com/2075-1729/12/8/1169, accessed on 23 August 2023). Briefly, the experimental field was located in the Novosibirsk region, Russia (54 • 4 6 N, 79 • 36 3 E) in the forest-steppe zone with a sharply continental climate and Luvic Endocalcic Chernozem (Siltic) [11] veing the most prevalent and agriculturally important soil of the region.…”
Section: Experimental Site and Conditionsmentioning
confidence: 99%